STRATEGI KOMUNIKASI PEMASARAN TERPADU (IMC) KEBUN RAYA EKA KARYA BALI DALAM MENINGKATKAN BRAND AWARENESS - Kartini, Ni Made; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia (E-Jurnal Medium, 2024)
The largest botanical garden in Indonesia and one of Bali's protected forests is Eka Karya Bali Botanical Garden. Located in the Bali Province's Candikuning Village, Baturiti District, and Tabanan District. Established in 1959, it has an area of 157.5 hectares and has a tagline “Let's go to the Botanical Garden”. Have brand awareness as a "Picnic and Education Recreation Area". The purpose of this study is to describe and explain the integrated marketing communication strategy (IMC) that has been implemented by Eka Karya Bali Botanical Garden in increasing brand awareness. This research uses a descriptive qualitative approach with the paradigm of post-positivism. Purposive sampling and snowball sampling are used in informant determination approaches. Information gathered through observation, documentation, and interviews. The findings of this study demonstrate that Eka Karya Bali Botanical Garden's integrated marketing communication strategy (IMC) combines a variety of promotions with the goal of raising brand awareness. Eka Karya Bali Botanical Garden uses the idea of the marketing mix, which consists of the four Ps: product, place, price, and promotion, to raise brand awareness. Advertising, sales promotion, interactive marketing, direct marketing, personal selling, public relations and publicity, events, and e-word of mouth are the eight components that make up the promotion mix. Keywords: Integrated Marketing Communication Strategy (IMC), Brand Awareness, Eka Karya Bali Botanical Garden, Marketing Mix, Promotion Mix.